2021
DOI: 10.2147/nss.s328774
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Sleepiness at the Wheel and Sleep-Related Car Accidents Among Patients with Obstructive Sleep Apnea: Data from the French Pays de la Loire Sleep Cohort

Abstract: Purpose: We aimed to determine the risk factors of sleepiness at the wheel among patients with obstructive sleep apnea (OSA) and to determine factors that were independently associated with reported sleep-related near-miss accidents or car accidents. Patients and Methods: This retrospective study was conducted on 843 OSA patients from the French Pays de la Loire sleep cohort database. Each patient completed surveys including anthropometric data, medical history, professional status, and data on alcohol and tob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
3
2
Order By: Relevance
“…The finding in this study was higher when compared with the other study conducted in Switzerland 5.1% [31], in Japan 2.5% [52], in Slovakia 10.2% [30], in Sweden 7.9% [28], in China 10.9% [53]. In contrast, this result was less than the other study conducted in France 28% [18], in Korea 19.1% [47], in Brazil 55.5% [21], in France 35.3% [22], in Belgium 50.8% [33] and 34.3% [27], in China 22.2% [24], in Greece 38.8% [54] and in Nigeria 44.8% [55]. The discrepancy might be a result of a difference in assessment tools, geographical areas, sample size, the nature and culture of the study subject, and the study setting.…”
Section: Smrcontrasting
confidence: 84%
See 2 more Smart Citations
“…The finding in this study was higher when compared with the other study conducted in Switzerland 5.1% [31], in Japan 2.5% [52], in Slovakia 10.2% [30], in Sweden 7.9% [28], in China 10.9% [53]. In contrast, this result was less than the other study conducted in France 28% [18], in Korea 19.1% [47], in Brazil 55.5% [21], in France 35.3% [22], in Belgium 50.8% [33] and 34.3% [27], in China 22.2% [24], in Greece 38.8% [54] and in Nigeria 44.8% [55]. The discrepancy might be a result of a difference in assessment tools, geographical areas, sample size, the nature and culture of the study subject, and the study setting.…”
Section: Smrcontrasting
confidence: 84%
“…Indirectly, the illness also leads other health problems like depression and/or anxiety, which can also cause EDS. Other study also reported that the association of EDS to younger age [20,52] male sex [49,52], smoking [18], high degree of job [22], insomnia [13,18], loud snoring [16,20,52], and multiple gestations [20]. Though, all the above factors were not independent predictors of EDS in our study, this might be due to variations in sample size, life style, health status, and sociocultural…”
Section: Smrcontrasting
confidence: 48%
See 1 more Smart Citation
“…Near-miss accidents were reported by 22% of patients reporting SW and were associated with ESS, depression, habitual sleep duration and the oxygen desaturation index (ODI) [37]. Compared to AHI, the severity of nocturnal hypoxia seems to be a better marker of daytime sleepiness [37][38][39] or poor performance at psychomotor vigilance tests [40]. The lack of a relationship between AHI and the risk for car accidents could at least partly be explained by the finding that OSA is not always associated with daytime sleepiness, as shown by recent studies on clinical OSA phenotypes [29,[41][42][43].…”
Section: Epidemiology Of Driving Accidents In the General Population ...mentioning
confidence: 99%
“…OSA is associated with significant health consequences, including hypertension, obesity, coronary artery disease, metabolic dysfunction, cognitive decline, and cancer progression [ 3 , 4 ]. Sleep-related accidents are also strongly associated with OSA [ 5 ].…”
Section: Introductionmentioning
confidence: 99%